2002
DOI: 10.1074/jbc.m201527200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Connection between the Yeast Cdc42 GTPase and the Slt2-mediated Cell Integrity Pathway Identified through the Effect of Secreted Salmonella GTPase Modulators

Abstract: Modulation of host cellular GTPases through the injection of the effector proteins SopE2 and SptP is essential for Salmonella typhimurium to enter into non-phagocytic cells. Here we show that expression of the guanine nucleotide exchange factor for Cdc42 SopE2 in Saccharomyces cerevisiae leads to the activation of Fus3 and Kss1 MAPKs, which operate in the mating and filamentation pathways, causing filamentous growth in haploid yeast cells. Furthermore, it promotes the activation of the cell integrity MAPK Slt2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 62 publications
3
36
0
Order By: Relevance
“…In the wild-type, incubation at 37 u C leads to an increase in the signal for phosphorylated Slt2 from that obtained at 28 uC in agreement with published data (Lagorce et al, 2003;Martin et al, 2000;Rodriguez-Pachon et al, 2002). Western blot analysis shows that, in contrast to the wildtype, in a prs1D strain the signal corresponding to phosphoSlt2 is stronger at 28 u C and is maintained over a period of 4 h during incubation at 37 u C (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…In the wild-type, incubation at 37 u C leads to an increase in the signal for phosphorylated Slt2 from that obtained at 28 uC in agreement with published data (Lagorce et al, 2003;Martin et al, 2000;Rodriguez-Pachon et al, 2002). Western blot analysis shows that, in contrast to the wildtype, in a prs1D strain the signal corresponding to phosphoSlt2 is stronger at 28 u C and is maintained over a period of 4 h during incubation at 37 u C (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Of the known PtdIns(3)P effector-domaincontain proteins in yeast, the PX-domain-containing Bem1p [a positive regulator of Cdc24p guanine-nucleotide exchange factor activity towards Cdc42p (Zheng et al, 1995)] and Bem3p [a GTPase-activating protein for Cdc42p (Zheng et al, 1994)] proteins could be attractive candidates for performing such a function. In line with this, it is noteworthy that a recent report from Molina and coworkers indicated that Cdc42p signaling can influence Slt2p activity (Rodriguez-Pachon et al, 2002). Therefore, it is intriguing that overexpression of BEM3 in ymr1⌬ sjl2 ts sjl3⌬ cells prevented growth at the normally permissive temperature of 34°C (our unpublished observations).…”
Section: Sydssupporting
confidence: 56%
“…Yersinia enterocolitica effectors, YopE, YopM, and YpkA, and Salmonella typhimurium effectors, SopE2, SptP, and SigD/SopB, were amplified by PCR using plasmids pCFL110, pCFL140, and pCFL150 (gifts of Dr. Samuel Miller), 9) and pKG-SopE2, pKG-SptP, and YCpLG-SigD (gifts of Dr. Maria Molina) 10,11) respectively. Oligonucleotides were designed so that their 3 0 ends were specific to the various pathogen effector genes and their 5 0 ends partially overlapped the sequences of the attB-adaptor primers, as described in the GatewayÔ technology instruction manual (Invitrogen) ( Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous effectors from various bacterial pathogens such as Yersinia, 8,9) Salmonella, 10,11) Pseudomonas, 12,13) Vibrio, 14) Legionella, 15,16) Campylobacter, 17) and Chlamydia 18,19) have been expressed in yeast and have been found to interfere with cellular functions related to their proposed targets within the host cell, such as Rho-type small GTPase, mitogen-activated protein kinase (MAPK) cascades, vesicle trafficking, DNA, the actin cytoskeleton, and microtubules. These reports indicate that the yeast system is powerful tool in the identification and characterization of pathogen effectors.…”
Section: 7)mentioning
confidence: 99%
See 1 more Smart Citation